Development of antioxidant packaging material based on optimized poly (lactic acid) and cellulose from durian rind biocomposites - Penjumras, Patpen (2018)
Durian rinds are the plant waste of durian fruit consumption. Only one-third of a durian is edible, whereas the seeds and the shell become waste. With regards to environmental impact, the waste can be converted into value-added products, such as cellulose, to be used as reinforcement material in biocomposites. Cellulose is extracted from ground durian rind using delignification with acidic sodium chlorite, followed by mercerization with sodium hydroxide. The diameter and aspect ratio of cellulose fibers are in the range of 100-150 μm and the aspect ratio is in the range of 20-25, which is higher than the minimum aspect ratio value for good strength transmission for any reinforcement. A central composite design was employed to determine the optimum preparation condition of the biocomposites to obtain the highest tensile strength and impact strength. The selected optimum condition was 35 wt.% cellulose loading at 165°C and 15 minutes of mixing, leading to a desirability of 94.6%. Under the optimum condition, the tensile strength and impact strength of the biocomposites were 46.21 MPa and 2.93 kJ/m2, respectively. The coupling agent 3-aminopropyltriethoxysilane (APS) was used to modify the surface of cellulose. The result found that silane-treated, cellulose-reinforced biocomposites offered superior mechanical properties compared with neat PLA and untreated cellulose-reinforced biocomposites. The adhesion of cellulose and the PLA matrix was improved by modifying the cellulose surface, which led to less water absorption into biocomposites. An antioxidant packaging material was developed using silane-treated durian rind cellulose reinforced poly(lactic acid) (PLA) biocomposites. The release of BHT and -tocopherol with 3 wt.% from neat PLA and biocomposites into two food simulants (50% and 95% ethanol in water) at two temperatures (27°C and 37°C) were monitored. The result found that BHT had a higher release rate than -tocopherol. At higher temperatures, the resulting release rate increased. Antioxidant was released from neat PLA faster than biocomposites. BHT released faster into 95% ethanol, while -tocopherol released faster into 50% ethanol. The faster release of antioxidant from each condition contributed to the inhibition of lipid oxidation, which was indicated by the decrease of peroxide value (PV) and thiobarbituric acid reactive substance (TBARS). It can be summarized that BHT had higher effectiveness as an antioxidant in active packaging application for edible oil. This study concluded that durian rind cellulose can be successfully used as a reinforcing material for poly(lactic acid) biocomposites. Its application, with the addition of antioxidants was seen to be an effective active packaging for the protection of edible oil from oxidation.